Table of Content - - (Journal of engineering sciences and information technology, 2024)
Table of Content: 1. Adaptive of the bee algorithm with an overall pattern extractor to improve the fingerprint matching process Ebrahim Omar Al Shami, Marah Bassem Ali 2. War disasters and their effects on urban structure, historic buildings, local people and architectural heritage Eng. Hussain Saleh Mohammed Al-Kawafi 3. Visual Pollution of Commercial Street Sidewalks: A Case Study of Design Standards in Al-Hilla City, Iraq Athraa Hamza Hussein, Mohammad Ali Al-Anbari 4. A Review on the Economic Assessment of Integrating Macro-Encapsulated Phase Change Material in Building Envelopes Amal Ahmed, Germin Elgohary, Ashraf Nessim 5. A Systematic Literature Review of Recent Blockchain Platforms Malak Sulaiman Alrumaih, Mohammad Mahdi Hassan Muhammad Ali Martuza, Suliman A. Alsuhibany 6. Optimization of Double-Skin Façades for Heating and Cooling in High-Rise Buildings: A Case Study in Kuwait City Eng. Fawaz Khaled Ghaith, Eng. Mohammad Hamad Buhamad